Association Analysis of COQ2 Variant in Dementia and Essential Tremor - Yin Xia Chao; Ebonne Yu Lin Ng; Huihua Li; Kandiah Nagaendran; Yuen Yih; Mei Sian Chong; Kumar M. Prakash; Louis Tan; Wing Lok Au; Yi Zhao; Zhi Dong Zhou; Murni Tio; et al. (Parkinson's Disease)
Objective. COQ2 mutations have been reported in Japanese multiple system atrophy (MSA) patients. We examined the role of COQ2 in patients with dementia and essential tremor (ET), two common neurodegenerative conditions. Materials & Methods. A total of 2064 subjects, including 560 patients with dementia, 466 patients with ET, and 1038 healthy controls, were included. Genotyping for the COQ2 V393A (T>C) was carried out. Odds ratio (OR) adjusted by age and gender, together with 95% confidence interval (CI), was reported by means of logistic regression. Results. The frequency of the polymorphic variant V393A heterozygous (T/C) was 2.7% in dementia, 1.1% in ET, and 2.5% in controls (OR = 0.70, 95% confidence interval is 0.29–1.72 for dementia, and OR = 0.47, 95% confidence interval is 0.17–1.31, p=0.1217 for ET). There was no significant association between V393A variant with dementia and ET. Conclusion. There was no significant association between V393A variant with dementia and ET. COQ2 gene is unlikely to play a significant role in patients with dementia or ET in our population.